Sobre a Fibra Especial de Ideais - Silva, Tarciana Maria Santos da (2010)
In this dissertation, we study Cohen-Macaulay and Gorenstein properties of the fiber cone of an ideal I of d-dimensional Cohen-Macaulay local ring (R,m).We also obtain a formula to express the multiplicity of the fiber cone of a m-primary ideal I in terms of mixed multiplicity ed−1(m|I) and superficial elements. As a consequence, we have that the Cohen-Macaulay properties of the fiber cone of I, with minimal mixed multiplicity and almost minimal, is characterized by the reduction number of I.